The impact of trade on income inequality in Mexico - Bernini, Andrea; J. de Groot, Olaf (Estudios Económicos de El Colegio de México, 2025)
Income inequality remains a significant concern in Mexico, despite a slight decrease in its measure in recent decades. This paper investigates the impact of changes in trade patterns resulting from the North American Free Trade Agreement (NAFTA) on income inequality in Mexico over the past 20 years. Through a decomposition into within- and between-sector inequality, this paper reveals that the contribution of the latter has increased in an environment characterized by decreasing overall income inequality. Trade accounts for approximately 14.5% of the total change in between-sector income inequality, representing the most substantial contribution among the factors identified in this study.